A Revision of the Nearctic Predaceous Midges in the Bezzia (Bezzia) pulverea complex (Diptera: Ceratopogonidae) - Grogan, Jr., William L. (Zootaxa, 2020)
This revision of the Nearctic predaceous midges in the Bezzia (Bezzia) pulverea complex (Diptera: Ceratopogonidae) recognizes 11 species, seven of which are new species: Bezzia (B.) amblystyla, n. sp., from Maryland and Florida; B. (B.) brunneipedia, n. sp., from Florida; B. (B.) folkersti n. sp., from Florida; B. (B.) huberti, n. sp., from Maryland, Florida, Arkansas and Louisiana; B. (B.) leptostyla, n. sp., from Florida; B. (B.) marylandensis, n. sp., from Maryland; and, B. (B.) titanochela, n. sp., from Texas, Alabama and Florida. Photomicrographs of diagnostic characters of both sexes are included, and a key is provided to adult males and females of species in the Bezzia (B.) pulverea complex. Bezzia (B.) imbifida Dow & Turner is transferred from the B. pulverea complex to the Bezzia (B.) expolita complex.